A hemocompatible polyurethane surface having dual fibrinolytic and nitric oxide generating functions. Issue 5 (16th January 2017) - Gu, Hao; Chen, Xianshuang; Liu, Xiaoli; Zhan, Wenjun; Lyu, Zhonglin; Yu, Qian; Wu, Zhaoqiang; Chen, Hong
Abstract : A multifunctional surface with fibrinolytic activity and the ability to inhibit SMC proliferation and platelet adhesion was realized. Abstract : Thrombus formation remains a serious problem in developing blood compatible materials. Despite continuous, intensive efforts over many years to prepare surfaces that prevent clotting, such surfaces have not been achieved; indeed it seems that surface-induced clotting is inevitable. An alternative approach is to accept that clotting will occur and to design surfaces so that small, nascent clots will be lysed before they can cause harm. The generation of plasmin, as in the fibrinolytic system, may be adopted for this purpose. The vascular endothelium (the inner surface of intact blood vessels) releases nitric oxide (NO) on a continuous basis. NO protects against platelet activation and aggregation, and also has an anti-proliferative effect on smooth muscle cells (SMCs). Based on these two important functions of the vascular system, the approach of constructing a fibrinolytic surface that generates NO is developed in the present work. Poly(oligo(ethylene glycol) methyl ether methacrylate- co -6-amino-2-(2-methacylamido)-hexanoic acid) (poly(OEGMA- co -LysMA)) was attached to a vinyl-functionalized polyurethane (PU) surface by graft polymerization giving a surface (PU-POL) with protein-resistant properties ( via poly(OEGMA)) and clot lysing properties ( via poly(LysMA)). Selenocystamine, which catalyzes S-nitrosothiol decomposition to generate NO in the vasculature, was then immobilized on the PU-POL surface via covalent attachment. A dual functioning surface with fibrinolytic activity (lysis of nascent clots) and NO releasing ability (inhibition of platelet adhesion and SMC adhesion as well as proliferation) was thereby constructed.